(untitled) (Third Sector Social Economic Review, 2024)
In order to ensure public investment expenditures and development, countries collect tax revenues directly and indirectly from real and legal persons and generate tax revenues. With the global system dominating the world, companies can now carry out their commercial activities in any country in the world. Countries now want to collect taxes at minimum rates not only from domestic companies but also from companies operating in their country and making commercial profits. These demands of countries make businesses want to shift their activities to countries where tax exemptions are high or called tax havens. International minimum corporate tax arises to legally secure tax revenue, as it aims to ensure that businesses pay tax in the country where the commercial activity takes place, in order to prevent their capital from shifting to tax haven countries. Since tax revenues constitute the largest item of income in Turkey, it is not desired to suffer corporate tax losses due to tax avoidance in our country. Turkey aims to prevent tax loss by creating a legal basis for global and domestic minimum corporate tax. The aim of this study is to examine the minimum corporate tax to be paid by corporate taxpayers in Turkey before and after the implementation of the domestic minimum corporate tax..